IMPLEMENTATION OF CONNECTED LEARNING PRINCIPLES IN TEACHING A FOREIGN LANGUAGE AT AN ENGINEERING UNIVERSITY - Zelenin, H. (Problems of Engineer-Pedagogical Education, 2023)
The article attempts to consider the topical issues of modern pedagogy: interactive forms and methods of optimizing the process of teaching a foreign language for special purposes in the context of higher engineering education, and peculiarities of distance and blended learning of a foreign language through the use of advanced information and communication technologies. Based on the analysis of the most recent research works in the field of innovations in teaching foreign languages, it is concluded that one of the most important directions is the introduction of modern information and communication technologies into the educational process, in particular technologies related to mobile learning, providing optimization of the educational process, accessibility and efficiency of learning, and students' integration into the information society. The author emphasizes that in the Englishlanguage methodological literature the designation of such a model of using electronic devices as "connected learning" is widely spread; defines the basic principles of "connected learning"; provides key advantages (intensification of independent activity, individualization of learning, increase of cognitive activity and motivation of learning, acquisition of skills and abilities, the formation and development of which on the basis of traditional teaching tools seems to be quite laborious) and disadvantages of active involvement of smartphones in the educational process (excessive emphasis on the technological filling of the educational process does not contribute to the development of logical and effective learning, reinforces students’ inclination to use conventional patterns in their thinking process, and even strengthens the habit of clip perception of reality, which is typical for the generation that grew up in the period of wide availability of the Internet and social networks). The article concludes that the practical application of mobile applications has a huge potential in improving the efficiency of the process of learning a foreign language for special purposes and can significantly improve the process of foreign language training of engineering students, open its new sides and turn it from a serious time-consuming process into an exciting activity, but it is necessary to carefully calibrate and integrate new mobile technologies into the educational process, and teachers should be properly prepared for the effective use of mobile technologies.